2009
DOI: 10.1007/s00784-009-0352-7
|View full text |Cite
|
Sign up to set email alerts
|

Intraseptal vs. periodontal ligament anaesthesia for maxillary tooth extraction: quality of local anaesthesia and haemodynamic response

Abstract: There is no data concerning the use of the intraseptal anaesthesia (ISA) for single tooth extraction. The aims of this study were to compare the clinical efficacy and haemodynamic responses of the ISA with the periodontal ligament anaesthesia (PLA) for single tooth extraction. Thirty-five randomly selected healthy patients (ASA I) undergoing maxillary lateral incisors extraction entered the study. Onset of anaesthesia, the width of the anaesthetic field and duration of anaesthesia were recorded by pinprick tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…However, factors such as inadequate choice of anesthetic solution, anesthetic salt overdose, accidental vasoconstrictor intravascular injection and fast administration of the solution may lead to increased blood concentration of the drug and to a higher potential for toxic effects 1,2 . Systemic complications of intravascular injection of local an-esthetics are basically induced by the interaction of adrenergic vasoconstrictors and sympathetic autonomous nervous system receptors, because its vasoconstrictor therapeutic action occurs by means of binding to α1 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…However, factors such as inadequate choice of anesthetic solution, anesthetic salt overdose, accidental vasoconstrictor intravascular injection and fast administration of the solution may lead to increased blood concentration of the drug and to a higher potential for toxic effects 1,2 . Systemic complications of intravascular injection of local an-esthetics are basically induced by the interaction of adrenergic vasoconstrictors and sympathetic autonomous nervous system receptors, because its vasoconstrictor therapeutic action occurs by means of binding to α1 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Niwa et al (27,28), showed that infiltration anesthesia for dental use with 3.6 mL of lidocaine with 1:80.000 epinephrine could be carried out safely on the patients who have exercise capacity of more than 4 metabolic equivalents. Brkovic et al (29) found no significant differences in the patients' hemodynamic response with lidocaine with epinephrine concerning the use of local anesthetic injection for single tooth extraction. Our results showed similarity to those by Perusse et al (17,20), who reported that the use of epinephrinecontaining local anesthetics in dental patients with coronary atherosclerosis could show significant hemodynamic changes and lead to life threatening complications.…”
Section: Discussionmentioning
confidence: 98%
“…Local clinical parameters of anesthesia were monitored only in healthy subjects through comparative analysis of two different anesthetics given by the same anesthetic technique or two different anesthetic techniques using the same anesthetic 12,13 . Two in vitro studies have recently demonstrated that antihypertensives propranolol and verapamil cause local anesthesia 14,15 .…”
Section: Discussionmentioning
confidence: 99%